COGNITIVE FEATURES OF CONTRARGUMENTATIVE DISCOURSE MARKERS IN MODERN SPANISH LANGUAGE - Lomakina , Irina (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The article deals with Spanish-language contrargumentative discourse markers as a separate class of expressions and words that perform common functions: they connect fragments of discourse, explain what semantic links exist between the text elements, manage the communication process, the interpretation of discourse by the speaker and the recipient, correlate, compare and contrast statements in discourse. These units not only syntactically combine parts of the text, but also explain the cognitive connections between its parts, as well as express the speaker's attitude to what he communicates, or his attitude to the speech addressee.Communicative implicatures can be blocked when the speaker realizes that his information has caused an undesirable effect in the mind of the interlocutor. The ability to understand this is determined as the theory of mind. An analysis of the cognitive functions of Spanish contrargumentative discourse markers reveals that they aim to refute undesired statements or assumptions.Contrargumentative DMs have their own program of functioning, according to which, they block the unwanted implicature that appeared in the previous statement, and on the other hand, they introduce a new block of discourse. With this new block, the communicator completes the information that the recipient should be left with. If we study the differences in the use of contrargumentative DMs, it is necessary to distinguish different shades of use within the limits of the above-mentioned algorithm. Awareness of these differences or shades of sense is usually inherent in native speakers and difficult to convey to those who are learning Spanish as a foreign language.___________References:• Lomakіna, І. «Semantiko-pragmatichnі osoblivostі diskursivnih markerіv u suchasnіj іspans'kіj movі [Semantic-pragmatic features of discourse markers in modern spanish language].» Problemi semantiki, pragmatiki ta kognіtivnoї lіngvіstiki [Problems of semantics, pragmatics and kognitive linguistics] 32 (2017) (In Ukr.).• Briz, A., Pons, S. y J., Portolés. Diccionario de partículas discursivas del español (2008), http://www.dpde.es• Escandell, Vidal, Leonetti,  «On the Rigidity of Procedural Meaning.» Procedural Meaning, Bingley, Emerald (2011): 81-102.• Martí Sánchez M. «Los marcadores discursivos para estudiantes y profesores.» Español como lengua extranjera. Actividades y claves realizadas por Sara Fernández Gómiz (Madrid: Edinumen, 2013).• Portolés, , Zorraquino, M. «Los marcadores del discurso.» (Madrid: Espasa Calpe, 1999), capítulo 63.• Nueva gramática de la lengua española, Real Academia española y asociación de academias de la lengua española (Madrid: Espasa, 2010_.• Schiffrin,  Discourse markers (Cambridge: Cambridge University Press, 1987), 364.
Keywords: contrargumentative discourse markers, discourse, cognitive functions, Spanish language, the theory of mind, implicature, communication